2023
DOI: 10.1111/jbg.12755
|View full text |Cite
|
Sign up to set email alerts
|

The effect of new and ancestral inbreeding on milk production traits in Iranian Holstein cattle

Abstract: Inbreeding depression, the reduction of fitness and performance, is due to an increase in the mating of related individuals. Based on the purge hypothesis, inbreeding and breeding over generations reduce the effect of deleterious alleles responsible for inbreeding depression. Thus, recent inbreeding is assumed to be more harmful than ancestral inbreeding. This study aimed at evaluating the effects of new and ancestral inbreeding on milk, fat and protein production in Iranian Holstein cattle. The secondary obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 90 publications
1
7
0
Order By: Relevance
“…This may indicate that the reduced lifetime production in German Brown cattle in this study is not only due to the shortened LPL, but the production traits themselves may be negatively influenced by inbreeding. This is in agreement with previous studies on different dairy cattle populations that reported inbreeding depression for milk performance in the first three lactations [6,[23][24][25]. The highest effects due to inbreeding depression, expressed in percentages of the genetic standard deviations, were demonstrated for LMY, Surv1, and EffLFY.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This may indicate that the reduced lifetime production in German Brown cattle in this study is not only due to the shortened LPL, but the production traits themselves may be negatively influenced by inbreeding. This is in agreement with previous studies on different dairy cattle populations that reported inbreeding depression for milk performance in the first three lactations [6,[23][24][25]. The highest effects due to inbreeding depression, expressed in percentages of the genetic standard deviations, were demonstrated for LMY, Surv1, and EffLFY.…”
Section: Discussionsupporting
confidence: 92%
“…Only few studies reported ancestral coefficients for different Holstein dairy cattle populations. The effects of the ancestral inbreeding coefficients on production, fertility, birth traits, and survival traits were not consistent [6,7,[23][24][25]. For example, in Irish and Dutch Holstein evidence of the presence of purging effects for production traits could be shown [6,23], whereas results for Canadian and Iranian Holstein were not significant or even contradictory [24,25].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Providing evidence of inbreeding purging is not only theoretically but also practically of great interest since populations less affected by inbreeding depression could be established if inbreeding purging exists. To date, many studies intending to detect inbreeding purging have been carried out in captive wild [10][11][12], domesticated animal [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] and human populations [30], some of which suggests the existence of inbreeding purging [10,12,15,17,28,30]. However, it has been also shown that inbreeding purging is not a ubiquitous phenomenon [10,12,31].…”
Section: Introductionmentioning
confidence: 99%
“…Genetic diversity enables genetic improvement of animal production traits and, therefore, is important both economically and environmentally [ 5 ]. On the contrary, increasing the inbreeding coefficient by 1% resulted in a reduction in milk, fat, and protein production by 11.99 kg, 0.39 kg, and 0.29 kg, respectively [ 6 ]. García-Ruiz et al [ 7 ] stated that at each percentage point of increase in inbreeding, milk, fat, and protein production decreased by 88 kg, 3.16 kg, and 2.57 kg, respectively.…”
Section: Introductionmentioning
confidence: 99%